Comparison of the Effects of Cyclophosphamide and Mycophenolate Mofetil Treatment Against Immunoglobulin G4-Related Disease: A Retrospective Cohort Study - Luo, Xuan; Peng, Yu; Zhang, Panpan; Li, Jieqiong; Liu, Zheng; Lu, Hui; Zhang, Xuan; Zeng, Xiaofeng; Zhang, Fengchun; Fei, Yunyun; Zhang, Wen (Frontiers in Medicine, 2020)
Background: Although there are multiple ways to manage immunoglobulin G4–related disease (IgG4-RD), including treatment with glucocorticoids, “steroid-sparing” immunosuppressive drugs, or biologic agents, few clinical trials on IgG4-RD have been conducted. This study aimed to compare the efficacy and safety of glucocorticoids (GCs) combined with cyclophosphamide (CYC) or mycophenolate mofetil (MMF) in IgG4-RD patients. This cohort study was registered at ClinicalTrials.gov (ID: NCT01670695). Methods: This retrospective study included 155 IgG4-RD patients who received GCs with CYC or MMF at the Department of Rheumatology at Peking Union Medical College Hospital between January 2012 and July 2018. Propensity score matching (PSM) was conducted to match two groups of patients based on their baseline clinical characteristics. Treatment response, relapse rate, and drug safety were analyzed. The treatment response was evaluated based on complete response (CR), partial response (PR), and no change (NC), and the cumulative relapse rate and adverse events in each treatment group were compared using Kaplan–Meier curves and log-rank test, respectively. Results: Of the 155 IgG4-RD patients, 90 were treated with GCs plus CYC (group I) and 65 with GCs plus MMF (group II). After propensity score–matched (PSM) analysis, 108 patients were selected (54 in each group), 49 of whom had “definite” IgG4-RD, 8 “probable” IgG4-RD, and 51 “possible” IgG4-RD. At the last follow-up, the total response in groups I and II was 98.15 and 96.3%, respectively, and within 12 months, the cumulative relapse rate in group II was significantly higher than that in group I (14.8 vs. 3.7%, P = 0.046). Recurrence occurred at the paranasal sinus, lacrimal glands, skin, lung, pancreas, and bile ducts, and the relapsed patients achieved remission after switching immunosuppressants or/and increasing the GC dose. Conclusions: In IgG4-RD patients with internal organ involvement, GCs plus CYC or MMF are both effective with similar effects in disease response, while GCs plus CYC reduced the relapse rate better than GCs plus MMF.